MiR-454-3p Promotes Oxaliplatin Resistance by Targeting PTEN in Colorectal Cancer - Qian, Xiao-Lan; Zhou, Fang; Xu, Song; Jiang, Jian; Chen, Zhi-Peng; Wang, Shao-Kai; Zuo, Yun; Ni, Chen (Frontiers in Oncology, 2021)
Colorectal cancer is one of the most common malignancies worldwide. Oxaliplatin is a first-line chemotherapeutic agent for treating advanced colorectal cancer. However, acquired resistance to oxaliplatin limits its therapeutic efficacy since the underlying mechanism remains largely unclear. In this study, we compared a panel of miRNA expression levels between oxaliplatin-sensitive and -resistant HCT-116 colorectal cancer cells, and found that miR-454-3p was the most differently expressed miRNAs and significantly up-regulated in oxaliplatin-resistant cells. Inhibition of miR-454-3p re-sensitized resistant cells to oxaliplatin and enhanced oxaliplatin-induced cellular apoptosis. Moreover, we determined that miR-454-3p promotes resistance to oxaliplatin through targeting PTEN and activating ATK signaling pathway. In vivo study revealed that overexpression miR-454-3p decrease the sensitivity of HCT-116 xenograft tumors to oxaliplatin treatment in mouse model. Clinically, high miR-454-3p expression was associated with a decreased responsiveness to oxaliplatin-based chemotherapy as well as a short progression-free survival (PFS). These data indicated that miR-434-3p might serve as a biomarker for predicting oxaliplatin sensitivity and a novel therapeutic target to overcome resistance to oxaliplatin in colorectal cancer.